A sensitive and specific assay for the serological diagnosis of antilaminin 332 mucous membrane pemphigoid. (1st November 2018) - Goletz, S.; Probst, C.; Komorowski, L.; Schlumberger, W.; Fechner, K.; van Beek, N.; Holtsche, M.M.; Recke, A.; Yancey, K.B.; Hashimoto, T.; Antonicelli, F.; Di Zenzo, G.; et al.
Summary: Background: Antilaminin 332 mucous membrane pemphigoid (MMP) is an autoimmune subepidermal blistering disease with predominant mucosal involvement and autoantibodies against laminin 332. Malignancies have been associated with this disease; however, no standardized detection system for antilaminin 332 serum antibodies is widely available. Objectives: Development of a sensitive and specific assay for the detection of antilaminin 332 antibodies. Methods: An indirect immunofluorescence (IF) assay using recombinant laminin 332 was developed and probed with a large number of antilaminin 332 MMP patient sera ( n = 93), as well as sera from patients with antilaminin 332‐negative MMP ( n = 153), bullous pemphigoid ( n = 20), pemphigus vulgaris ( n = 20) and noninflammatory dermatoses ( n = 22), and healthy blood donors ( n = 100). Results: In the novel IF assay, sensitivities with the laminin 332 heterotrimer and the individual α3, β3 and γ2 chains were 77%, 43%, 41% and 13%, respectively, with specificities of 100% for each substrate. The sensitivity for the heterotrimer increased when an anti‐IgG4 enriched antitotal IgG conjugate was applied. Antilaminin 332 reactivity paralleled disease activity and was associated with malignancies in 25% of patients with antilaminin 332 MMP. Conclusions: The novel IF‐based assay will facilitate the serological diagnosis of antilaminin 332 MMP and may help to identify patients at risk of a malignancy. Abstract : What's already known about this topic? Antilaminin 332 mucous membrane pemphigoid (MMP) is an autoimmune subepidermal blistering disease with predominant mucosal involvement characterized by antilaminin 332 autoantibodies. Malignancies have been associated with this disease, but currently no standardized detection system for antilaminin 332 serum antibodies is widely available. What does this study add? A sensitive and highly specific immunofluorescence assay for the detection of antilaminin 332 autoantibodies using recombinant laminin 332‐expressing human cells was developed, which will soon be widely available. What is the translational message? This assay may not only facilitate the diagnosis of antilaminin 332 MMP but may also be valuable to monitor disease activity and identify patients at risk of a malignancy. Respond to this article